An experimental study on the performance of a zinc air fuel cell with inexpensive metal oxide catalysts and porous organic polymer separators - Sapkota, P.; Kim, H. (ELSEVIER SCIENCE INC, 2010)
A zinc air fuel cell (ZAFC) of taper-end structure was designed and manufactured with a polyamide-base engineering plastic. An air cathode with multiple layers of blended inexpensive metal oxides, MnO2 and CeO2, showed a remarkably stable electricity-generating performance even at high current density. A cheap thin Nylon filter was found as a potential candidate for the separator in ZAFC because of its high stability and durability in the alkali electrolyte and proper pore size. ？ 2010.